The Media in Malaysia: Aspirations, Choices and Realities - Ramli Mohamed; Adnan Hussein (Kajian Malaysia, 2006)
The papers in this volume were presented at the 15th Asian Media Information and Communication Centre (AMIC) Conference on ''Media in Asia: Aspirations, Choices and Realities'', organised in collaboration with Universiti Sains Malaysia (USM) in Penang, 17–20 July 2006. The conference was attended by 250 delegates from 30 countries who presented a total of 189 papers. The opening was officiated by Y.B. Datuk Wong Kam Hoong, the Deputy Minister of the Ministry of Culture, Arts and Heritage and attended by the Secretary-General of ASEAN, H.E. Ong Keng Yong and the Assistant Secretary-General for Communication & Information of UNESCO, Dr. Abdul Waheed Khan.